Pengembangan Evaluasi Pembelajaran IPAS Berbasis Quizizz Untuk Meningkatkan Motivasi dan Prestasi Belajar Kelas V SDN Karanganyar di Jember - Zidni, Sinar Rosidah; Ubaidillah, Sofwan Roif (Pendidikan Islam Pascasarjana IAIN Jember, 2024)
The development of Quizizz-based Science Learning Evaluation is to make it easier for teachers to evaluate learning because there is no need to correct it manually. The development of this evaluation is to increase student motivation and achievement while learning is taking place. The objectives of developing learning evaluation are (1) Describe the development of quizizz-based science learning evaluation for class V students at SDN Karanganyar 01 Jember. (1) Describe the validation of quizizz-based science learning evaluation for class V students at SDN Karanganyar 01 Jember. (2) Describe the effectiveness of using Quizizz-based science learning evaluation to increase motivation and learning achievement of class V students at SDN Karanganyar 01 Jember. This research uses the Borg and Gall Research Development model, with 10 steps, namely: (1) research and data collection, (2) planning, (3) product draft development, (4) initial field trials, (5) revising test results trial, (6) field trials, (7) product refinement resulting from field trials, (8) field implementation trials, (9) refinement of resulting products, (10) dissemination and implementation. The results of the development research can be concluded: The Quizzizz-based science learning evaluation product meets the validity criteria, with material expert validation results of 89%, media expert validation of 87%, language expert validation of 91%. The results of the validity of the question items were 6 invalid questions and 14 valid questions. Reliability results 0.934. Difficulty level 14 easy and 6 questions very easy. The power test differentiated 4 questions very bad, 1 question very bad, 1 question fair, 8 questions good, and 6 questions very good. The results of the pretest field trials were 64% and posttest 90%. The results of the pretest learning achievement were 68% and posttest 95%. The independent sample T-Test is 0.000, so Ho is rejected and Ha is accepted. The conclusion is that using quizizz-based learning evaluation media gets a higher average score compared to the pretest or before using quizizz-based learning evaluation media.